Electrodialysis Desalination with Simultaneous pH Adjustment Using Bilayer and Bipolar Membranes, Modeling and Experiment - Elena Nosova; Aslan Achoh; Victor Zabolotsky; Stanislav Melnikov (Membranes, 2022)
A kinetic model of the bipolar electrodialysis process with a two-chamber unit cell formed by a bilayer (bipolar or asymmetric bipolar) and cation-exchange membrane is proposed. The model allows describing various processes: pH adjustment of strong electrolyte solutions, the conversion of a salt of a weak acid, pH adjustment of a mixture of strong and weak electrolytes. The model considers the non-ideal selectivity of the bilayer membrane, as well as the competitive transfer of cations (hydrogen and sodium ions) through the cation-exchange membrane. Analytical expressions are obtained that describe the kinetic dependences of pH and concentration of ionic components in the desalination (acidification) compartment for various cases. Comparison of experimental data with calculations results show a good qualitative and, in some cases, quantitative agreement between experimental and calculated data. The model can be used to predict the performance of small bipolar membrane electrodialysis modules designed for pH adjustment processes.